MEASUREMENT OF D2O IN WATER USING 2H(?,n)1H REACTION (Journal of Sciences, Islamic Republic of Iran)
Utilization of Photodisintegration reaction of Deuterium, 2H(?,n)1H, is a precise technique for determining the percentage of 2H in tritiated and natural water. The 23Na(n,?)24Na reaction is a suitable ?-source for producing the 2H(?,n)1H reaction. Tehran Research Reactor was used as a neutron source for producing 24Na isotopes. The BF3 detectors were used to detect the neutron emission of H2 content of water. We obtained a linear calibration plot by repeating the experiment with many samples of different concentrations of tritiated water. With this simple portable apparatus which have been used for this purpose for the first time, and corresponding linear plot, we can monitor and determine easily and accurately the 2H concentration of an unknown sample.